Readings on The old man and the sea - Szumski, Bonnie (San Diego, CA : Greenhaven, 1999)
A collection of essays by various authors which offer analysis and criticism on a novel by Ernest Hemingway.
Includes bibliographical references and index.
10-A.
Keywords: Hemingway, Ernest, -- 1899-1961.; Hemingway, Ernest, -- 1899-1961.; Fishing stories, American -- History and criticism; Fables, American -- History and criticism; Aged men in literature; Fables -- History and criticism; Elderly men in literature